Corrections to "Vanishing Morrey integrability for Riesz potentials in Morrey-Orlicz spaces" - Mizuta, Yoshihiro; Shimomura, Tetsu (MATHEMATICA SCANDINAVICA, 2023)
In this note some flaws in our recent paper by Mizuta and Shimomura (Math. Scand. 129 (2023), no. 2, 374–400) are corrected.